Differences in the Effectiveness of Tamarind Turmeric Herbal Drink and Warm Compresses on Primary Dysmenorrhea Pain Intensity in Adolescent Women - Hidayati, Tutik; Hanifah, Iis (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Dysmenorrhea, or pain during menstruation, can significantly disrupt a woman's daily life. This pain often affects the activities of young women. In Indonesia, it is widely believed that consuming tamarind turmeric herbal drinks and using warm compresses can help alleviate the pain associated with primary dysmenorrhea. This study aimed to compare the effectiveness of tamarind turmeric herbal drinks and warm compresses in reducing the intensity of primary dysmenorrhea pain in adolescent girls. The study included 52 female students from Probolinggo Unggulan Senior High School who had a history of dysmenorrhea, with a sample size of 42 students who experienced menstruation in April–May 2023 and met the inclusion criteria. The research utilized a quasi-experimental analytical approach and a probability sampling technique. The results of the t-test showed significant differences in the effectiveness of tamarind turmeric herbal drinks and warm compresses on the intensity of primary dysmenorrhea pain in young women. Based on these findings, it is recommended that warm compresses be used as the primary alternative for treating primary dysmenorrhea pain in order to minimize disruption to daily activities